KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP BERDASARKAN GENDER - Suswigi Suswigi; Ulfa Septiani; Muhammad Salimul Farhan; Tomi Suparman Awal Purnama; Irmina Monte; Wahyu Hidayat (Departement of Mathematics Education, 2019)
This research is qualitative research with correlation method aims to analyze students' mathematical communication skills in solving problems that are viewed from gender. The selection of research subjects using purposive sampling technique based on sex with the procedure for selecting research subjects, namely, choosing male and female students. Then a written test was carried out in the form of a test of mathematical communication skills, then the test results were analyzed. The population in this study were all seventh grade students in the 2017/2018 school year at one of the junior high schools in Cimahi City. While the study sample was taken one class randomly from the whole class VII, namely class VII A totaling 30 students consisting of 15 male students and 15 female students. Measurement of mathematical communication skills of students in this study using a test instrument in the form of a set of questions in the form of a description without any prior learning as many as 5 questions. Giving a description question aims to see the process of students' abilities, accuracy and systematic arrangement of answers that can be seen from each step of solving the problem made. This test of mathematical communication skills was developed by researchers for social arithmetic material as the first step taken in compiling questions is to make a grid, arrange questions and answer keys and determine the score of each item in question. The results of the correlation test and the percentage of tests of mathematical communication skills from this study are that there is an influence of gender on the mathematical communication skills of junior high school students with the results of mathematical communication skills of male students classified as moderate with an average value of 57.47%, while the mathematical communication abilities of female students are classified high with an average percentage value of 65.73%